Image-Guided Resuscitation With Limited Transthoracic Echocardiogram in Pediatric Trauma Patients. Issue 2 (February 2018) - Plant, Valerie; Vanguri, Poornima; Anand, Rahul; Haynes, Jeffrey; Aboutanos, Michel; Ferrada, Paula
Abstract : Introduction: Limited transthoracic echocardiogram (LTTE) has been shown to be a useful tool in guiding resuscitation in adult trauma patients. Our hypothesis is that image-guided resuscitation in pediatric trauma patients with LTTE is feasible. Methods: A retrospective chart review was performed on highest level pediatric trauma alerts (age 18 years or younger) at our level I trauma center during a 6-month period. Patients were divided into 2 groups as follows: those who had LTTE performed (LTTE group) and those who did not have LTTE performed (non-LTTE group). Results: A total of 31 charts were reviewed; 4 patients were excluded because they died on arrival to the emergency department. Fourteen patients had LTTE performed (LTTE group); 13 patients did not have LTTE performed (non-LTTE group). There was no difference in mechanism of injury, age, injury severity score, weight, or intensive care unit admission between the groups. The LTTE group received significantly less intravenous fluid than the non-LTTE group (1.2 vs 2.3 L, P = 0.0013).Within the LTTE group, 8 patients had "full" inferior vena cava (IVC) and 6 patients had "empty" IVC. There was no difference in injury severity score between these subgroups ( P = 0.1018). Less fluid was given in the group labeled with full IVC [1.1 L (0.8–1.2)] than the group with empty IVC [2.4 L (1.7–2.6)], P = 0.0005. Four of the 6 patients with "empty" IVC had a confirmed source of bleeding. Conclusions: Limited transthoracic echocardiogram can limit the amount of unnecessary crystalloid resuscitation given to pediatric trauma patients who are not hypovolemic.